DERADIKALISASI IDEOLOGI GERAKAN ISLAM - Muhsin Mahfudz (ILMU POLITIK UNIVERSITAS ISLAM NEGERI (UIN) ALAUDDIN MAKASSAR, 2010)
Radical Islam movement had been a parth of Islamic history since the emergence of Khawarij movement in about 37 AH. or 657/658 AD. This article tries to identify the genealogy of Islamic radicalism from Khawarij movement to Bali bombing by Imam Samudera abd his friends. By using the historical analysis method, this article focuses on their ideology that encouraged them to be martyr (syahid). As a result, I discovered that the radical movement they did was based on both political and textual understanding backgrounds. To minimize the power of those backgrounds, the article tries to formulate two approaches which is called 'moderate interpretation' and 'multiculturalism'. The first aproach is set to encounter scriptural and textual understanding in justifying a holy text, while the second is set to give an alternative view from political frame to cultural frame. Those aproaches are considered more significant to solve any scepticism among people about the ligitimacy of religion on culture of violence. Keywords: Radical, Radikalisasi, Ideologi, Islam, Teks, Multikulturalisme